Lateralized brain activities in subcortical vascular mild cognitive impairment with differential Chinese medicine patterns: A resting-state functional magnetic resonance imaging study - Wang, Jianjun; Kong, Fanxin; Zheng, Haotao; Cai, Dongbin; Liu, Lijin; Lian, Jie; Lyu, Hanqing; Lin, Songjun; Chen, Jianxiang; Qin, Xiude (Frontiers in Neuroscience, 2022)
Background: Subcortical vascular mild cognitive impairment (svMCI) is one of the most treatable cognitive impairments, but could be hampered by the high clinical heterogeneities. Further classification by Chinese Medicine (CM) patterns has been proved to stratify its clinical heterogeneities. It remains largely unknown of the spontaneous brain activities regarding deficiency patterns (DPs) and excess patterns (EPs) of svMCI patients based on fMRI data. Objective: We aim to provide neuroimaging evidence of altered resting-state brain activities associated with DPs and EPs in svMCI patients. Methods: Thirty-seven svMCI patients (PAs) and 23 healthy controls (CNs) were consecutively enrolled. All patients were categorized into either the EP group (n = 16) and the DP group (n = 21) based on a quantitative Chinese medicine scale. The fractional amplitude of low-frequency fluctuation (fALFF) value was used to make comparisons between different subgroups. Results: The DP group showed significant differences of fALFF values in the right middle frontal gyrus and the right cerebellum, while the EP group showed significant differences in the left orbitofrontal gyrus and the left cerebellum, when compared with the CN group. When compared with the EP group, the DP group had markedly increased fALFF values in the left superior temporal gyrus, right middle temporal gyrus and brainstem. The decreased fALFF values was shown in the right anterior cingulate and paracingulate gyri. Among the extensive areas of frontotemporal lobe, the Montreal Cognitive Assessment (MoCA) scores were significantly correlated with the reduced fALFF value of the right middle frontal gyrus and the left orbitofrontal gyrus. Conclusion: Our results indicated that the DPs and EPs presented the lateralization pattern in the bilateral frontal gyrus, which will probably benefit the future investigation of the pathogenesis of svMCI patients.